EFEKTIVITAS PENINDAKAN PELANGGARAN LALU LINTAS BERDASARKAN PASAL 265 AYAT (1) UNDANG â UNDANG NOMOR 22 TAHUN 2009 GUNA MENINGKATKAT KESELAMATAN LALU LINTAS DI SURAKARTA - Setiawan, Nanang Heri (Fakultas Hukum Universitas Sebelas Maret, 2014)
This study aims to describe how the effectiveness of Article 265 ( 1 ) of Law No. 22 of 2009 on Traffic and Road Force as a law enforcement efforts to improve Traffic safety is a factor in Surakarta legislation. Then, which factors can be influence effectiveness of Article 265 ( 1 ) of Law No. 22 of 2009. And, which effort can do for increase traffic accident at teenager.This research is a descriptive law. The author uses the type of empirical studies / sociology. Primary data were obtained from the data sources in the field, while the secondary data obtained from the books, materials and a bibliography of references that support research. The author uses data collection techniques such as field studies, literature studies, interviews.Based on the research results Article 265 ( 1 ) of Law No. 22 of 2009, not effective for increase traffic accident in Surakarta. The total number of violations are in 2010 year: 22.920, 2011 year: 46.170, 2012 year: 45.510. Factors that influence are legislation factor, law enforcement factor , factor means or facility law enforcement , community factors , cultural factors . Efforts are being made to improve the safety of Traffic Police in Surakarta is necessary to become a police community mempolisikan for himself , the dissemination of traffic safety pioneer of early to students , increase patrols at vulnerable , execute the operation or inspection of motor vehicles .